Estimating the depths of shallow waters using landsat thematic mapper data the case of the Kalayaan Island Group - Balais, Benjamin P. (2000)
In an effort to address the considerable lack of baseline information on the Kalayaan Island Group (KIG) in which the Philippines is one of the claimants, this paper synthesizes the capability of some advanced technologies to provide information on the bathymetry of some unknown shallow areas. These technologies include remote sensing, geographic Information system (GIS) and statistical tools to predict the depths of the shallow portion of the KIG. The study makes use of landsat Thematic Mapper (TM) data and available nautical charts as inputs to the multiple regression analysis model to generate a bathymetric map of the study area. This paper also explores the use of other surface interpolation methods and compares the results with the regression model and the known depths. The regression model is subjected to a number of standard statistical test. Result of the F-test shows that there is a functional dependence of depths on the independent variables (Landsat Band 1 signal and bottom characteristics). Analysis of the partial regression coefficients, including the standardized coefficients, indicate that depth exhibits dependency on bottom classes that are shallower than 16 fathoms. Results show that shallow portions corresponding to classes 3 to 6 (rock-coral, calcareous rock, rock-and-sand-rubble and coraline sand) are very important in determining the depths.